Detection of water vapor and some gases using a semiconductor laser - Ammar Zaker; Mozahem Azzawi (College of Education for Pure Sciences, 2007)
Abstract A laser sensor was designed in this work in order to detect water vapour and some chosen gases for the enviromented pollution or in the field of meteorology . The gases that had been studied were , , and . The results had been pointed out that the gas gave the lowest attenuation on laser radiation , while the gas the largest attenuation . we were able to detect the of an amount (23.5) part in athousant of volume when passing through the gas chamber in per second .